Formulation and Development of Fast Dissolving Oral Film of a Poorly Soluble Drug Piroxicam with Improved Drug Loading Using Mixed Solvency Concept and its Evaluation - Carpenter, Garima (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present research work is to explore the application of mixed solvency to formulate and develop a fast dissolving oral film of piroxicam with improved drug loading utilizing the mixed-solvency concept. Materials and Methods: All solubilizers sodium benzoate, polyethylene glycol (PEG) 400, and polyvinylpyrrolidone (PVP) K30 were weighed accurately and transferred in a 100 ml beaker. Then, warm and demineralized water sufficient to dissolve the solubilizers were added. After complete dissolution of solubilizers, 200 mg of piroxicam was dissolved in the above solution, and temperature was maintained at 55–60°C so as to facilitate the evaporation of water. Then, this viscous mass was poured on the already prepared backing layer (having polymer ratio polyvinylalcohol [PVA] 14000: PVP K 30 [40:60] and 5% w/w PEG 400 as plasticizer) in Petri plate and spread with spreader. The prepared film was dried in an oven at 40°C for 24 h. The prepared films were kept in desiccators and used for further studies. Results and Discussion: On the basis of solubility studies, the blend containing PVP14000 + PEG 400 + SB (13.3:13.3:13.3) was selected. For formulation development, backing layer containing polymer ratio PVA 14000:PVP K 30 (40:60) was found to be most appropriate. PEG 400 5% w/w provides faster dissolution of the prepared backing layer as well as better tensile strength. FD 8 batch showed better evaluation results and was taken as the optimized batch. Dissolution profiles of piroxicam pure drug, optimized fast dissolving oral film, fast dissolving oral film with perforations and marketed dispersible tablet (Pirox DT) were compared and results showed that dissolution rate of piroxicam from fast dissolving oral film was similar to marketed dispersible tablet (Pirox DT). Conclusion: From all the above studies, it was concluded that the approach of mixed solvency is novel, safe, cost-effective, and user-friendly. It also eliminates the problem of toxicity associated with high concentration of single solubilizers. Hence, it may be employed in dosage form development of drugs where fast onset of action is desired. It may also enhance the bioavailability associated with poor dissolution of drug.